Catalyst for preparing aldehyde and / or ketone through direct catalytic dehydrogenation of alcohol as well as preparation method and application of catalyst

By supporting the active metal Me on hydroxyapatite HAP under oxygen-free conditions and forming a catalyst for amorphous HAP coating, the cost, selectivity and stability of the anaerobic alcohol dehydrogenation catalytic system in the prior art is solved. The problem of efficient, stable and selective alcohol-direct catalytic dehydrogenation reaction is achieved.

CN119455995APending Publication Date: 2025-02-18UNIV OF SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411651305.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When the prior art is directly catalyzed for alcohol dehydrogenation under anaerobic conditions, the catalytic system is still in the laboratory research and development stage due to problems such as cost, selectivity or stability, and is still a certain distance away from industrial application.

Method used

A catalyst was designed to form a composite Me/HAP of an amorphous HAP cladding by supporting the active metal Me on hydroxyapatite HAP and activate in the presence of alcohol under an oxygen-free conditions.

Benefits of technology

The efficiency, stability and selectivity of alcohol-direct catalytic dehydrogenation under anaerobic conditions are achieved, and the catalyst has long catalytic life and good industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455995A_ABST
    Figure CN119455995A_ABST
Patent Text Reader

Abstract

The invention relates to a catalyst for preparing aldehyde and / or ketone through direct catalytic dehydrogenation of alcohol, and a preparation method and application thereof. The catalyst comprises a compound Me / HAP and an amorphous HAP coating layer, wherein the compound Me / HAP is formed by loading active metal Me on hydroxyapatite HAP, and the active metal Me is coated with the amorphous HAP coating layer. The catalyst Me (at) HAP can be directly used for a reaction for preparing aldehyde and / or ketone through direct catalytic dehydrogenation of alcohol, and the catalyst can also be formed in situ at the temperature of 180-350 DEG C by using the compound Me / HAP in the reaction for preparing aldehyde and / or ketone through direct catalytic dehydrogenation of alcohol, so that preparation of aldehyde and / or ketone through direct catalytic dehydrogenation of alcohol is realized. The amorphous HAP coating layer on the active metal Me not only can avoid aggregation and growth of metal particles in the reaction process, but also can stabilize the overall structure of the catalyst, so that the catalyst disclosed by the invention has excellent stability, high alcohol conversion rate, high aldehyde ketone selectivity and long catalytic life in the direct catalytic dehydrogenation reaction; good industrial application prospects are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalytic dehydrogenation under anaerobic conditions, and in particular to a catalyst for preparing aldehydes and / or ketones by direct catalytic dehydrogenation of alcohol under anaerobic conditions, and a preparation method and application thereof. Background Art

[0002] Aldehydes and ketones are oxygenated compounds with high value and wide application. They are important fine chemicals and also raw materials for many high value-added products. Currently, most of them are obtained through the selective oxidation of fossil-based alcohols. Compared with oxidative dehydrogenation, anaerobic direct dehydrogenation technology has the advantages of high selectivity, 100% atomic utilization, no need to use oxidants with certain hazards or pollution, no byproduct H2O, and reduced impact on catalyst stability. The key to anaerobic dehydrogenation depends on the design and preparation of efficient and highly stable catalysts. Due to the advantages of easy separation and reuse and low environmental pollution, heterogeneous catalysts have broad application prospects.

[0003] In recent years, scientists have focused their research on the design of catalysts for the oxidant-free direct dehydrogenation of alcohol compounds. The catalytic metals cover almost all common IB and VIII groups, among which precious metals such as Pt, Pd, and Ru, and non-precious metals such as Cu, Ni, and Co have been widely studied due to their high activity. Although the current research on the anaerobic dehydrogenation of alcohols to produce aldehydes and ketones for the co-production of hydrogen has achieved certain results, the relevant catalytic system is still in the laboratory research and development stage due to cost, selectivity, or stability issues. It will be significantly deactivated in a short period of time and is still a long way from industrial application. Therefore, it is urgent to develop and design efficient catalysts for anaerobic dehydrogenation reactions. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a metal catalyst with high catalytic activity, high stability, environmental friendliness and easy industrialization for direct catalytic dehydrogenation of alcohols to prepare aldehydes and / or ketones under anaerobic conditions.

[0005] To this end, in one aspect, the present invention provides a catalyst for direct catalytic dehydrogenation of alcohols to prepare aldehydes and / or ketones, the catalyst comprising: a composite Me / HAP formed by supporting an active metal Me on hydroxyapatite HAP; and an amorphous HAP coating layer formed on the active metal Me of the composite Me / HAP, wherein the amorphous HAP coating layer is formed by activating the composite Me / HAP in the presence of alcohol at a temperature of 180-350° C. under anaerobic conditions.

[0006] In a preferred embodiment, the active metal Me is one or more selected from Pd, Ir, Pt, Ru, Cu, Zn, Ni, Co and Fe.

[0007] In a preferred embodiment, the content of the active metal Me is 0.1-20 wt % relative to the total weight of the catalyst.

[0008] In a preferred embodiment, the amorphous HAP coating is porous.

[0009] In a preferred embodiment, the alcohol as a raw material is the same as or different from the alcohol used for the activation treatment and is one or more selected from ethanol, n-butanol, sec-butanol, 1,2-propylene glycol, 2,3-butanediol, benzyl alcohol, cyclohexanol, isopropanol and glycerol.

[0010] In another aspect, the present invention provides a method for preparing the above-mentioned catalyst, the method comprising: dissolving a soluble salt of an active metal Me in a solvent to form a soluble salt solution, and impregnating hydroxyapatite HAP into the soluble salt solution to load the active metal Me on the HAP; calcining the obtained solid phase and then reducing it under a hydrogen atmosphere to obtain a composite Me / HAP; and activating the composite Me / HAP in the presence of alcohol at a temperature of 180-350°C under anaerobic conditions to form an amorphous HAP coating layer on the active metal Me of the composite Me / HAP, thereby obtaining the desired catalyst Me@HAP.

[0011] In a preferred embodiment, the formation of an amorphous HAP coating layer on the active metal Me of the Me / HAP composite is achieved in situ in the reaction of direct catalytic dehydrogenation of alcohols to produce aldehydes and / or ketones under anaerobic conditions.

[0012] In a preferred embodiment, the soluble metal salt concentration of the soluble salt solution is 3-12 mol / L and the immersion time is 12-48 h;

[0013] In a preferred embodiment, the solid phase is obtained by centrifugation;

[0014] In a preferred embodiment, the obtained solid phase is dried before calcination.

[0015] In a preferred embodiment, the drying is performed at 20-120°C for 6-12 h;

[0016] In a preferred embodiment, the calcination temperature is 250°C-550°C;

[0017] In a preferred embodiment, the reduction is carried out at a temperature of 200-550° C. for 1-6 h.

[0018] In another aspect, the present invention provides a method for preparing aldehydes and / or ketones by direct catalytic dehydrogenation of alcohols, the method comprising: in a fixed bed reactor, in the presence of the above catalyst or the catalyst prepared according to the above method, subjecting the alcohol as a raw material to a direct dehydrogenation reaction at a temperature of 150-350° C. under anaerobic conditions, thereby obtaining the desired aldehyde and / or ketone products.

[0019] In another aspect, the present invention provides a method for preparing aldehydes and / or ketones by direct catalytic dehydrogenation of alcohols, the method comprising: reacting alcohol as a raw material at a temperature of 180-350° C. under anaerobic conditions in the presence of the above-mentioned composite Me / HAP in a fixed bed reactor, wherein an amorphous HAP coating layer is in situ formed on the active metal Me of the composite Me / HAP during the reaction, thereby obtaining the desired aldehyde and / or ketone products.

[0020] In a preferred embodiment, the alcohol used as a raw material is one or more selected from ethanol, n-butanol, sec-butanol, 1,2-propylene glycol, 2,3-butanediol, benzyl alcohol, cyclohexanol, isopropanol and glycerol.

[0021] In a preferred embodiment, the alcohol as a raw material is injected into the mixture at a rate of 0.5-10 h. -1 The liquid hourly space velocity LHSV is fed into the fixed bed reactor.

[0022] In a preferred embodiment, the catalyst is used in a particle size of 20-30 mesh.

[0023] The present invention obtains a catalyst Me@HAP having an amorphous HAP coating layer formed on the active metal Me by activating a composite Me / HAP (which is reduced in a hydrogen atmosphere after calcination) loaded on the active metal Me under anaerobic conditions at a temperature of 180-350°C in the presence of alcohol.

[0024] The catalyst Me@HAP of the present invention can not only be directly used for the reaction of direct catalytic dehydrogenation of alcohol to prepare aldehydes and / or ketones, but also the catalyst of the present invention can be formed in situ by using the composite Me / HAP at a temperature of 180-350° C. in the reaction of direct catalytic dehydrogenation of alcohol to prepare aldehydes and / or ketones under anaerobic conditions, thereby realizing direct catalytic dehydrogenation of alcohol to prepare aldehydes and / or ketones. The amorphous HAP coating layer on the active metal Me can not only avoid the aggregation and growth of metal particles during the reaction process but also stabilize the overall structure of the catalyst, so that the catalyst of the present invention has excellent stability, high alcohol conversion rate, high aldehyde and / or ketone selectivity and long catalytic life in the direct catalytic dehydrogenation reaction, and has good industrial application prospects.

[0025] In addition, in the direct catalytic dehydrogenation reaction of the above alcohols, the catalyst of the present invention also has the advantages of high product selectivity, simple preparation process, relatively mild reaction conditions, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 shows a high-resolution transmission electron microscopy (HR-TEM) image of the catalyst 5Cu@HAP prepared according to the present invention;

[0027] Figure 2 The X-ray diffraction (XRD) patterns of the hydroxyapatite (HAP) used in the present invention and the coating layer of the catalyst 5Cu@HAP prepared therefrom are shown;

[0028] Figure 3 The high-angle annular dark field scanning transmission electron microscopy (HADDF-STEM) image of the catalyst 5Cu@HAP prepared according to the present invention is shown;

[0029] Figure 4 The HADDF-STEM spectrum of the coating structure of the catalyst 5Cu@HAP prepared according to the present invention is shown;

[0030] Figure 5 Element mapping (EDS) spectrum of the catalyst 5Cu@HAP prepared according to the present invention, which mainly includes the EDS spectrum of the species elements Cu, Ca, O and P on the support surface.

[0031] Figure 6 The HADDF-STEM images of the coating layer structures of other catalysts 5Zn@HAP, 10Co@HAP, 1Pd@HAP and 5Fe@HAP prepared according to the present invention are shown.

[0032] Figure 7 The attenuated total reflection Fourier transform infrared (ATR-IR) spectra of the catalyst 5Cu@HAP prepared according to the present invention before and after adsorption of the sec-butanol substrate are shown. DETAILED DESCRIPTION

[0033] Based on extensive and in-depth research, the inventors found that hydroxyapatite (HAP), which is usually used as a carrier, has both acidity and alkalinity and can be changed by adding heterologous metals. At the same time, phosphate can change the electronic environment of the exogenous metal, and HAP has a strong metal ion adsorption capacity, which can make the loaded metal disperse very well and show high catalytic activity, so that the catalytic reaction can be carried out under relatively mild temperature conditions, with a relatively high conversion rate and high selectivity. Moreover, due to the alkalinity of HAP, the adsorption and activation of substrate alcohols in the reaction process can be significantly promoted.

[0034] Further, the inventors unexpectedly found that when alcohol contacts the above-mentioned composite Me / HAP under specific conditions, specifically when alcohol contacts the above-mentioned composite Me / HAP under anaerobic conditions at a temperature of 180-350°C, it will be adsorbed on the active metal Me and the carrier HAP at the same time, and as the alcohol adsorbed on the HAP migrates to the active metal Me, the HAP will be activated and driven to migrate to the surface of the active metal Me, thereby forming an amorphous coating layer on the surface of the active metal Me. Without being bound by any theory, the inventors refer to this phenomenon as a strong metal-carrier interaction caused by the activation treatment induced by the reactants. Moreover, when the composite Me / HAP having an amorphous HAP coating layer on the active metal Me obtained after the above-mentioned activation treatment is used as a catalyst for direct catalytic dehydrogenation of alcohol to prepare aldehydes and / or ketones (hereinafter referred to as catalyst Me@HAP), the above-mentioned amorphous HAP coating layer (preferably porous) will not hinder the adsorption of the active site to the reaction substrate molecules and thus will not reduce the catalytic activity of the active metal (i.e., still maintain high catalytic dehydrogenation activity). At the same time, due to the strong metal-support interaction, the obtained catalyst Me@HAP can not only have a good activation effect on carbon-hydrogen bonds and oxygen-hydrogen bonds, but the formed coating layer unexpectedly also leads to additional effects including but not limited to the following: first, the coating layer can inhibit the product from contacting the active site and avoid the production of coupled by-products, thereby improving the selectivity of alcohol dehydrogenation; second, the coating layer can prevent the metal from sintering and deactivation during the reaction process, thereby ensuring that the catalyst activity is not affected; third, the coating layer enhances the overall stability of the metal-loaded composite Me / HAP, making the active metal more stable and less likely to be lost, and thus making the catalyst life longer (>500 h). Therefore, the catalyst Me@HAP of the present invention can achieve stable and efficient direct catalytic dehydrogenation of alcohol under anaerobic conditions.

[0035] Based on the above findings, the catalyst for direct catalytic dehydrogenation of alcohol to prepare aldehydes and / or ketones provided by the present invention comprises: a composite Me / HAP formed by supporting an active metal Me on hydroxyapatite HAP; and an amorphous HAP coating layer formed on the active metal Me of the composite Me / HAP, wherein the amorphous HAP coating layer is formed by activating the composite Me / HAP in the presence of alcohol at a temperature of 180-350° C. under anaerobic conditions.

[0036] As used herein, alcohol refers to a compound with one or more hydroxyl (OH) groups. Generally speaking, the present invention has no particular limitation on the alcohol used, which may be, for example, a monohydric alcohol, a dihydric alcohol, an aromatic alcohol, etc. Preferably, the alcohol used for activation treatment or as a raw material for catalytic dehydrogenation in the present invention may be the same or different, and more preferably is selected from one or more of ethanol, n-butanol, sec-butanol, 1,2-propylene glycol, 2,3-butanediol, benzyl alcohol, cyclohexanol, isopropanol and glycerol.

[0037] As used herein, hydroxyapatite has the chemical formula Ca 10 (PO4)6(OH)2 and is referred to herein as HAP.

[0038] As used herein, Me / HAP refers to a composite of metal Me supported on a carrier HAP (sometimes also referred to as a "catalyst precursor"), and Me@HAP refers to a desired catalyst having an amorphous HAP coating layer formed on the active metal Me of the composite Me / HAP.

[0039] As used herein, anaerobic conditions refer to conditions in which there is no oxygen (sometimes even no oxidizing species). For example, in the present invention, anaerobic conditions can be achieved by directly injecting alcohol into a reactor or reaction equipment at a desired temperature to form an anaerobic alcohol atmosphere. Additionally or alternatively, anaerobic conditions can be achieved at room temperature by first replacing the atmosphere in the reactor or reaction equipment with an inert gas such as nitrogen or argon to form an inert atmosphere, and therefore inert atmosphere is sometimes referred to or used herein to indicate anaerobic conditions.

[0040] As used herein, an amorphous HAP coating refers to a HAP coating formed when the composite Me / HAP is activated by alcohol under the above-mentioned specific conditions (i.e., in the absence of oxygen or in an inert atmosphere at a temperature of 180-350°C), and HAP migrates to the surface of the metal Me. The HAP coating is an amorphous or non-crystalline coating, and is generally a porous coating. The specific conditions for forming an amorphous HAP coating on the active metal Me of the composite Me / HAP are a combination of the following: (1) an oxygen-free atmosphere or an inert atmosphere; (2) the presence of an alcohol substrate; and (3) a temperature of 180-350°C. The present inventors have found that such an amorphous HAP coating is not formed in an oxygen atmosphere and / or in the absence of an alcohol substrate, and even when the first two conditions are met, if the temperature is lower than 180°C or higher than 350°C, the desired amorphous HAP coating is not formed.

[0041] In the present invention, the active metal Me that can be used is preferably one or more selected from Pd, Ir, Pt, Ru, Cu, Zn, Ni, Co and Fe.

[0042] In the present invention, preferably, the content of active metal Me is 0.1-20 wt %, more preferably 0.1-10 wt %, relative to the total weight of the catalyst. The present inventors have found that within such an active metal content range, not only the required high performance of the catalyst can be maintained, but also it is cost-effective.

[0043] The catalyst provided by the present invention can be prepared by the following method: first, a soluble salt of an active metal Me is dissolved in a solvent to form a soluble salt solution, and hydroxyapatite HAP is impregnated into the soluble salt solution to load the active metal Me on the HAP; then, the obtained solid phase is calcined and then reduced under a hydrogen atmosphere to obtain a composite Me / HAP; finally, under anaerobic conditions, the obtained composite Me / HAP is activated in the presence of alcohol at a temperature of 180-350°C to form an amorphous HAP coating layer on the active metal Me of the composite Me / HAP, thereby obtaining the desired catalyst Me@HAP.

[0044] In the present invention, as an alternative or preferred embodiment, the formation of an amorphous HAP coating layer on the active metal Me of the composite Me / HAP can be achieved in situ in the reaction of direct catalytic dehydrogenation of alcohols to prepare aldehydes and / or ketones under anaerobic conditions. As used herein, the term "in situ" means that the above-mentioned amorphous HAP coating layer does not need to be formed in advance, but is formed along with the reaction when the reaction reaches the above-mentioned specific conditions for forming the amorphous HAP coating layer.

[0045] In the present invention, preferably, the soluble metal salt concentration of the formed soluble salt solution may be, for example, 3-12 mol / L, and at such a concentration, the immersion time of HAP may be, for example, 12-48 h.

[0046] In the present invention, preferably, the solid phase in the solution formed after the impregnation can be easily obtained by a technique known in the art such as centrifugal separation.

[0047] In the present invention, preferably, the separated solid phase can be dried before calcination to facilitate the calcination process. More preferably, the drying can be performed at 20-120° C. for 6-12 h.

[0048] In the present invention, preferably, the calcination may be performed, for example, in a muffle furnace at a temperature of 250-550° C. for 1-8 h.

[0049] In the present invention, preferably, the calcined solid phase is subjected to a reduction treatment, usually in a hydrogen atmosphere at a temperature of 200-550° C. for 1-6 h, thereby obtaining the desired composite Me / HAP. In addition, as known in the art, the active metal Me after such a reduction treatment is usually nanoparticles, and its particle size is, for example, in the range of about 1-100 nm.

[0050] In the present invention, after obtaining the desired composite Me / HAP, in order to form an amorphous HAP coating layer on the active metal Me of the composite Me / HAP, this can be achieved by subjecting the obtained composite Me / HAP to an activation treatment at a temperature of 180-350° C. in the presence of alcohol under anaerobic conditions, or by directly placing the obtained composite Me / HAP into a reactor (usually a fixed bed reactor) for performing a reaction of directly catalytic dehydrogenation of alcohol to prepare aldehydes and / or ketones under anaerobic conditions.

[0051] Based on the catalyst of the present invention, the present invention provides a method for directly catalytically dehydrogenating alcohol to prepare aldehydes and / or ketones, comprising: in a fixed bed reactor, in the presence of the above catalyst or the catalyst prepared according to the above method, subjecting the alcohol as a raw material to a direct dehydrogenation reaction at a temperature of 150-350° C. under anaerobic conditions, thereby obtaining the desired aldehyde and / or ketone products.

[0052] As an alternative or preferred embodiment, another method for preparing aldehydes and / or ketones by direct catalytic dehydrogenation of alcohols provided by the present invention comprises: in a fixed bed reactor, in the presence of the above-mentioned composite Me / HAP, reacting alcohol as a raw material at a temperature of 180-350° C. under anaerobic conditions, wherein in the reaction, an amorphous HAP coating layer is in situ formed on the active metal Me of the composite Me / HAP, thereby obtaining the desired aldehyde and / or ketone products.

[0053] In the present invention, there is no particular limitation on the type of reactor, and preferably the reactor may be a fixed bed reactor, for example a tubular fixed bed reactor made of stainless steel or quartz with an inner diameter of about 20 mm and a length of about 50 cm.

[0054] In the present invention, there is no particular limitation on the alcohol as a raw material, and preferably, the alcohol as a raw material may be one or more selected from ethanol, n-butanol, sec-butanol, 1,2-propylene glycol, 2,3-butanediol, benzyl alcohol, cyclohexanol, isopropanol and glycerol.

[0055] In the present invention, preferably, the alcohol as a raw material can be injected into the mixture at a rate of 0.5-10 h. -1 , more preferably 2-5h -1 The liquid hourly space velocity (LHSV) is fed into the fixed bed reactor.

[0056] In the present invention, preferably, the catalyst Me@HAP or the composite Me / HAP can be used with a particle size of 20-30 mesh, for example. In addition, there is no particular limitation on the loading amount of the catalyst or the composite, for example, about 30 g of the catalyst Me@HAP or the composite Me / HAP can be loaded into the fixed bed reactor.

[0057] In the present invention, preferably, another valuable product, hydrogen, can be obtained by gas phase collection, separation and purification using techniques known in the art.

[0058] Example

[0059] The present invention will be described in detail below by non-limiting examples. These examples are only non-limiting examples for illustrating the specific implementation and realization process of the present invention, and are not intended to limit the scope of the present invention.

[0060] In the following examples, unless otherwise specified, the equipment, reagents and raw materials used are all commercially available, or can be synthesized or prepared by methods known in the art, and the purchased reagents or raw materials can be used directly without further treatment, or after drying or other dehumidification treatment. Similarly, unless otherwise specified, the reaction processes and treatment methods involved are all known in the art or belong to routine operations.

[0061] Preparation Example 1: Preparation of Catalyst 5Cu@HAP

[0062] First, in a 1L round-bottom flask, 5.778 g of copper nitrate (Sinopharm Chemical Reagent Co., Ltd.) was weighed and dissolved in 7.5 g of distilled water to form a copper nitrate solution. Then, 30 g of commercially purchased HAP (Shanghai Aladdin Biochemical Technology Co., Ltd.) was immersed in the solution for 15 h to load metal Cu onto HAP.

[0063] Then, the solid phase was separated by centrifugation (speed of 900 r / min) and dried in a drying oven (Anhui Ke Mi Instrument Co., Ltd.) at 70 °C for 6 h. After that, the dried solid phase was calcined in a muffle furnace (Anhui Ke Mi Instrument Co., Ltd.) at 500 °C in air for 2 h, and then reduced in a hydrogen atmosphere at 350 °C for 2 h, thereby obtaining a composite Cu / HAP supported on metal copper.

[0064] Next, under normal pressure, the resulting composite Cu / HAP was placed in a stainless steel tubular fixed bed reactor (Anhui Kemi Instrument Co., Ltd.) with an inner diameter of 20 mm and a length of 50 cm, and the temperature inside the reactor was controlled at about 200°C by internal self-contained electric heating, and then ethanol was injected through an injection pump for activation treatment for about 2 hours to form a HAP coating layer on the surface of the metal Cu particles, thereby obtaining the desired catalyst. Based on calculations, the copper loading or content in the catalyst is 5 wt%, so it is counted as 5Cu@HAP, see Table 1 below.

[0065] The intermediate composites and the final catalysts obtained above were characterized and analyzed by high-resolution transmission electron microscopy (HR-TEM), X-ray diffraction (XRD), high-angle annular dark-field scanning transmission electron microscopy (HADDF-STEM) and elemental mapping (EDS).

[0066] Figure 1 The high resolution transmission electron microscopy (HR-TEM) image of the composite 5Cu@HAP prepared according to the present invention is shown. Figure 1 It can be seen that the active metal Cu particles are supported on rod-shaped hydroxyapatite (HAP), and the Cu particles are nanoparticles with a particle size of about 5 nm.

[0067] Figure 2 The X-ray diffraction (XRD) patterns of the hydroxyapatite (HAP) used in the present invention and the coating layer of the catalyst 5Cu@HAP prepared therefrom are shown. Figure 2 It can be seen that compared with the XRD pattern of HAP, there is no obvious diffraction peak related to metal Cu in the XRD pattern of the obtained catalyst 5Cu@HAP, indicating that the metal Cu nanoparticles are uniformly dispersed on HAP.

[0068] Figure 3 The high angle annular dark field scanning transmission electron microscopy (HADDF-STEM) spectrum of the composite 5Cu / HAP prepared according to the present invention is shown, and Figure 4 The HADDF-STEM spectrum of the coating structure of the catalyst 5Cu@HAP prepared according to the present invention is shown. Figure 3 and Figure 4 It can be seen from the comparison that compared with Figure 3 The product of Figure 4 The product in the process forms a coating layer on the metal Cu particles; at the same time, Figure 4 It can be further seen that Figure 4The coating layer formed by the product on the metal Cu nanoparticles has no obvious lattice fringes, indicating that the coating layer is an amorphous or non-crystalline (porous) structure, that is, an amorphous coating layer structure is formed on the surface of the Cu nanoparticles loaded on HAP.

[0069] Figure 5 The EDS spectrum of the catalyst 5Cu@HAP prepared according to the present invention mainly includes the EDS spectrum of the species elements Cu, Ca, O and P on the surface of the carrier. Figure 5 The element distribution of the obtained catalyst 5Cu@HAP can be clearly seen. Figure 1-5 Overall, it can be confirmed that in the obtained catalyst 5Cu@HAP, the active metal Cu is coated with HAP, that is, an amorphous HAP coating layer is formed on the surface of the metal Cu nanoparticles.

[0070] Preparation Example 2-17

[0071] The same procedure as described in Preparation Example 1 was followed, except that the type and amount of active metal and the corresponding preparation process conditions were changed according to Table 1 below, to prepare the catalysts in Table 1.

[0072] Table 1

[0073]

[0074] The prepared catalysts were characterized in the same manner as in the preparation examples. Figure 6 The HADDF-STEM spectra of the catalysts 5Zn@HAP, 10Co@HAP, 1.0Pd@HAP and 5Fe@HAP prepared according to the present invention are shown. These characterization results all indicate that each of these catalysts prepared according to the present invention forms an amorphous HAP coating layer on the surface of the metal Me particles of its corresponding composite Me / HAP.

[0075] Application Example 1: Direct catalytic dehydrogenation of ethanol to produce acetaldehyde under anaerobic conditions

[0076]

[0077] In a stainless steel tubular fixed bed reactor (inner diameter 20 mm, length 50 cm), 30 g of the catalyst 5Cu@HAP (particle size 20-30 mesh) obtained in Preparation Example 1 was loaded under nitrogen atmosphere (oxygen-free conditions), and the temperature inside the reactor was controlled at about 300°C by internal self-powered heating. Then, the reactor was heated at 3 h by a syringe pump. -1Ethanol (commercially available, anhydrous) as a raw material was injected into the reaction at a liquid hourly space velocity of 1.50 and the reaction was kept at normal pressure for 12 hours. After the reaction was completed, the liquid phase product and the gas phase product were collected separately through gas-liquid separation.

[0078] The collected liquid products were analyzed by gas chromatography, and the analysis results are shown in Table 2. The gas chromatography conditions used were as follows: GC1690 gas chromatograph FID detector, capillary column (Innowax, 30m×0.250mm×0.25um), programmed temperature rise, the initial column temperature was 50°C, the temperature was increased to 250°C at a rate of 10°C / min and maintained for 10 minutes. The carrier gas was 99.99% high-purity N2, and the flow rate was 1ml / min.

[0079] Application Example 2-9: Direct catalytic dehydrogenation of ethanol to produce acetaldehyde under anaerobic conditions

[0080]

[0081] The same procedure as in Application Example 1 was followed, except that the catalyst 5Cu@HAP in Application Example 1 was replaced with other catalysts shown in Table 2 below, and the reaction temperature and the feed liquid hourly space velocity of the raw alcohol were changed. Gas chromatography analysis was also performed after the reaction was completed, and the results are shown in Table 2.

[0082] Table 2

[0083]

[0084] Application Example 10-18: Direct catalytic dehydrogenation of n-butanol to produce n-butyraldehyde under anaerobic conditions

[0085]

[0086] The same procedure as in Application Example 1 was used, except that the raw material was changed to n-butanol, and the catalyst, reaction temperature, and feed liquid hourly space velocity of the raw material alcohol were used as shown in Table 3. Gas chromatography analysis was also performed after the reaction was completed, and the results are shown in Table 3.

[0087] Table 3

[0088]

[0089] Application Example 19-27: Direct catalytic dehydrogenation of sec-butyl alcohol to produce 2-butanone under anaerobic conditions

[0090]

[0091] The same procedure as in Application Example 1 was used, except that the raw material was changed to sec-butyl alcohol, and the catalyst, reaction temperature, and feed liquid hourly space velocity of the raw material alcohol were used as shown in Table 4. Gas chromatography analysis was also performed after the reaction was completed, and the results are shown in Table 4.

[0092] Table 4

[0093]

[0094] also, Figure 7 The Fourier transform attenuated total reflection infrared spectra of the catalyst 5Cu@HAP according to the present invention before and after adsorption of sec-butyl alcohol substrate are shown. Figure 7 It can be seen that before and after the adsorption of sec-butyl alcohol, at the wave number of 3321 cm -1 The vibration peak of the corresponding alcohol hydroxyl group was adsorbed on 5Cu@HAP and a peak of about 24 cm -1 The red shift (about 3345cm -1 ), indicating that the catalyst of the present invention forms chemical adsorption with the substrate alcohol, thereby confirming that the coating layer formed on the active metal of the catalyst of the present invention does not affect the adsorption of the reactant molecules.

[0095] Application Example 28-36: Direct catalytic dehydrogenation of 1,2-propylene glycol to acetol under anaerobic conditions

[0096]

[0097] The same procedure as in Application Example 1 was followed except that the raw material was changed to 1,2-propylene glycol, and the catalyst, reaction temperature, and feed liquid hourly space velocity of the raw material alcohol were used as shown in Table 5. Gas chromatography analysis was also performed after the reaction was completed, and the results are shown in Table 5.

[0098] Table 5

[0099]

[0100] Application Examples 37-45: Direct catalytic dehydrogenation of 2,3-butanediol to acetoin under anaerobic conditions

[0101]

[0102] The same procedure as in Application Example 1 was followed except that the raw material was changed to 2,3-butanediol and the catalyst, reaction temperature and feed liquid hourly space velocity of the raw material alcohol were used as shown in Table 6. Gas chromatography analysis was also performed after the reaction was completed, and the results are shown in Table 6.

[0103] Table 6

[0104]

[0105] Application Examples 46-54: Direct catalytic dehydrogenation of benzyl alcohol to benzaldehyde under anaerobic conditions

[0106]

[0107] The same procedure as in Application Example 1 was followed, except that the raw material was changed to benzyl alcohol, and the catalyst, reaction temperature, and feed liquid hourly space velocity of the raw alcohol were used as shown in Table 7. Gas chromatography analysis was also performed after the reaction was completed, and the results are shown in Table 7.

[0108] Table 7

[0109]

[0110] Application Examples 55-63: Direct catalytic dehydrogenation of other alcohols to ketones under anaerobic conditions

[0111] The same procedure as in Application Example 1 was used, except that the raw materials were changed to cyclohexanol, isopropanol, and glycerol, and the catalysts, reaction temperatures, and feed liquid hourly space velocity of the raw alcohol were used as shown in Table 8 below. Gas chromatography analysis was also performed after the reaction was completed, and the results are shown in Table 8.

[0112] Table 8

[0113]

[0114] Application Example 64: Direct catalytic dehydrogenation of ethanol to produce acetaldehyde under anaerobic conditions

[0115]

[0116] In a stainless steel tubular fixed bed reactor (inner diameter 20 mm, length 50 cm), 30 g of the intermediate composite 5Cu / HAP (particle size 20-30 mesh) obtained in Preparation Example 1 was charged under nitrogen atmosphere (anaerobic condition), and the temperature inside the reactor was controlled at about 300°C by electric heating. Then, the mixture was heated by a syringe pump at a rate of 3 h. -1 Ethanol (commercially available, anhydrous) was injected as a reaction raw material at a liquid hourly space velocity of 1.5 mol / L and the reaction was kept at normal pressure for 12 h. After the reaction was completed, the liquid phase product and the solid phase catalyst were separated and collected.

[0117] The collected liquid products were analyzed by gas chromatography, and the analysis results are shown in Table 9 below. The gas chromatography conditions used were as follows: GC1690 gas chromatograph FID detector, capillary column (Innowax, 30m×0.250mm×0.25um), programmed temperature rise, the initial column temperature was 50°C, the temperature was increased to 250°C at a rate of 10°C / min and maintained for 10 minutes. The carrier gas was 99.99% high-purity N2, and the flow rate was 1ml / min.

[0118] In addition, the results of HADDF-STEM analysis of the collected solid phase catalysts are consistent with Figure 4 This indicates that the intermediate complex 5Cu / HAP used forms an amorphous HAP coating layer on the metal Cu particles in situ during the reaction, that is, the catalyst 5Cu@HAP with an amorphous HAP coating layer formed on the metal particles as described in the present invention is still the one that actually plays a catalytic role in the reaction.

[0119] Application Examples 65-69: Direct catalytic dehydrogenation of ethanol to produce acetaldehyde under anaerobic conditions

[0120]

[0121] The same procedure as in Application Example 1 was followed except that the catalyst 5Cu / HAP in Application Example 1 was replaced by other composite intermediates shown in Table 9 below, and the reaction temperature and the feed liquid hourly space velocity of the raw material alcohol were changed. Gas chromatography analysis was also performed after the reaction was completed, and the results are shown in Table 9.

[0122] Table 9

[0123]

[0124] In addition, the results of HADDF-STEM analysis confirmed that the catalysts actually playing the catalytic role in the above reactions were the corresponding catalysts of the present invention having an amorphous HAP coating layer formed on the metal particles.

[0125] Application Examples 70-74: Direct catalytic dehydrogenation of n-butanol to produce n-butyraldehyde under anaerobic conditions

[0126]

[0127] The same procedure as in Application Example 64 was followed, except that the raw material was changed to n-butanol, and the catalyst, reaction temperature, and feed liquid hourly space velocity of the raw material alcohol were used as shown in Table 10. Gas chromatography analysis was also performed after the reaction was completed, and the results are shown in Table 10.

[0128] Table 10

[0129]

[0130] The results of HADDF-STEM analysis confirmed that the catalysts actually playing the catalytic role in the above reactions were the corresponding catalysts of the present invention having an amorphous HAP coating layer formed on the metal particles.

[0131] Application Examples 75-82: Evaluation of the Stability / Lifetime of 5Cu@HAP Catalyzed Dehydrogenation of Sec-Butanol to 2-Butanone

[0132] The same procedure as in Application Example 1 was followed, except that the raw material was changed to sec-butyl alcohol and the reaction was carried out for different reaction times. Gas chromatography analysis was performed after different reaction times. The results are shown in Table 11.

[0133] Table 11

[0134]

[0135] It can be seen from Table 11 that the catalyst Me@HAP provided by the present invention has excellent stability and long catalytic life in the reaction of direct catalytic dehydrogenation of alcohols to prepare aldehydes and / or ketones under anaerobic conditions.

[0136] In addition, the above experimental results show that the catalyst Me@HAP provided by the present invention can be used to prepare the desired aldehyde and / or ketone products with high conversion rate and high selectivity in the reaction of direct catalytic dehydrogenation of alcohol to prepare aldehyde and / or ketone under anaerobic conditions under relatively mild conditions. At the same time, the use of the catalyst of the present invention makes the preparation process simple, the reaction equipment simple, the operation easy, the product and the catalyst easy to separate, the catalyst cheap and easy to obtain, the catalyst stability and recycling performance are good, and it is suitable for industrial production and has a very broad application prospect.

[0137] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to provide those skilled in the art with an understanding of the content of the present invention and to implement it accordingly, and are not exhaustive of specific implementation methods, and cannot be used to limit the protection scope of the present invention. Any modification or equivalent replacement according to the technical solution of the present invention, without departing from the purpose and scope of the technical solution of the present invention, shall be included in the scope of the claims of the present invention.

Claims

1. A catalyst for direct catalytic dehydrogenation of alcohols to prepare aldehydes and / or ketones, the catalyst comprising: The active metal Me is loaded on hydroxyapatite HAP to form a composite Me / HAP; and forming an amorphous HAP coating layer on the active metal Me of the composite Me / HAP, The amorphous HAP coating layer is formed by activating the composite Me / HAP in the presence of alcohol at a temperature of 180-350° C. under anaerobic conditions.

2. The catalyst according to claim 1, characterized in that The active metal Me is one or more selected from Pd, Ir, Pt, Ru, Cu, Zn, Ni, Co and Fe; preferably, the content of the active metal Me is 0.1-20 wt % relative to the total weight of the catalyst.

3. The catalyst according to claim 1 or 2, characterized in that The amorphous HAP coating is porous.

4. A method for preparing a catalyst according to any one of claims 1 to 3, the method comprising: Dissolving a soluble salt of active metal Me in a solvent to form a soluble salt solution, and impregnating hydroxyapatite HAP into the soluble salt solution to load the active metal Me on the HAP; The obtained solid phase is calcined and then reduced under a hydrogen atmosphere, thereby obtaining a composite Me / HAP; as well as Under oxygen-free conditions, the composite Me / HAP is activated in the presence of alcohol at a temperature of 180-350° C. to form an amorphous HAP coating layer on the active metal Me of the composite Me / HAP, thereby obtaining the desired catalyst Me@HAP.

5. The method according to claim 4, characterized in that The formation of an amorphous HAP coating layer on the active metal Me of the Me / HAP composite is achieved in situ in the direct catalytic dehydrogenation of alcohols to produce aldehydes and / or ketones under oxygen-free conditions.

6. The method according to claim 4, characterized in that The soluble metal salt concentration of the soluble salt solution is 3-12 mol / L and the immersion time is 12-48 h; Preferably, the solid phase is obtained by centrifugal separation; Preferably, the obtained solid phase is dried before calcination, more preferably the drying is carried out at 20-120°C for 6-12 h; Preferably, the calcination temperature is 250°C-550°C; Preferably, the reduction is carried out at a temperature of 200-550° C. for 1-6 h.

7. A method for preparing aldehydes and / or ketones by direct catalytic dehydrogenation of alcohols, the method comprising: In a fixed bed reactor, in the presence of a catalyst according to any one of claims 1 to 3 or a catalyst prepared by the method according to any one of claims 4 to 6, an alcohol as a raw material is subjected to a direct dehydrogenation reaction at a temperature of 150-350° C. under oxygen-free conditions, thereby obtaining the desired aldehyde and / or ketone products.

8. A method for preparing aldehydes and / or ketones by direct catalytic dehydrogenation of alcohols, the method comprising: In a fixed bed reactor, in the presence of the composite Me / HAP according to claim 1 or claim 4, alcohol as a raw material is reacted at a temperature of 180-350° C. under anaerobic conditions, wherein an amorphous HAP coating layer is in situ formed on the active metal Me of the composite Me / HAP during the reaction, thereby obtaining the desired aldehyde and / or ketone products.

9. The method according to claim 7 or 8, characterized in that: The alcohol used as a raw material is one or more selected from ethanol, n-butanol, sec-butanol, 1,2-propylene glycol, 2,3-butanediol, benzyl alcohol, cyclohexanol, isopropanol and glycerol.

10. The method according to claim 9, characterized in that The alcohol as raw material was injected into the -1 The liquid hourly space velocity LHSV is fed into the fixed bed reactor; preferably, the catalyst is used with a particle size of 20-30 mesh.